Diaphragm for lithium ion battery and preparation method of diaphragm

By using vacuum impregnation technology of modified barium titanate and perfluoroethylene propylene copolymer on the lithium-ion battery separator, the existing separator has been solved and the mechanical properties of the separator are improved. and safety performance.

CN119481585AActive Publication Date: 2025-02-18CHANGZHOU INST OF TECH RES FOR SOLID STATE LIGHTING +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411615012.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators will shrink at high temperatures, causing contact between positive and negative electrodes, causing safety problems, and have poor liquid absorption capacity and insufficient mechanical strength.

Method used

The separator paper matrix is ​​made of polyolefin fibers, cellulose fibers and dispersants, and the mixed slurry layer is vacuum impregnated on its surface. The mixed slurry layer is made of phenolic resin, curing agent, ceramic powder, and modified barium titanate. Consisting of perfluoroethylene propylene copolymer, modified barium titanate is modified by KH550 to improve dispersion and interface effect.

Benefits of technology

It improves the toughness, mechanical properties and high temperature resistance of the diaphragm, avoids battery short circuit caused by lithium dendrites, enhances the safety performance and service life of the battery, and reduces friction loss inside the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

According to the diaphragm for the lithium ion battery and the preparation method of the diaphragm, the main body base material is selected from the cellulosic fibers doped with the polyolefin fibers, so that the toughness and the mechanical property of the diaphragm can be improved, battery short circuit caused by lithium dendrite puncture can be effectively avoided, the safety performance of the lithium ion battery is improved, and the service life of the lithium ion battery is prolonged; the doped ceramic powder can further improve the mechanical property and the high temperature resistance of the diaphragm, meanwhile, a coating process is omitted, and the efficiency is improved; barium titanate is modified by adopting KH550, so that the dispersity of barium titanate is improved, the interface interaction between barium titanate and resin is enhanced, and the gas production problem of inorganic powder in the battery using process is solved; the perfluoroethylene propylene copolymer is added, so that the friction coefficient of the diaphragm can be reduced, and the friction loss in the battery can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium primary batteries, and specifically relates to a diaphragm for lithium ion batteries and a preparation method thereof. Background Art

[0002] In recent years, the automobile industry has developed rapidly, but it has also brought negative impacts such as environmental pollution and rapid consumption of oil resources, so all countries are actively developing electric vehicles. Among them, lithium-ion batteries are the main power source of electric vehicles. Lithium-ion batteries are generally composed of three main parts: positive electrode, negative electrode, and diaphragm carrying electrolyte. As one of the important components of lithium-ion batteries, the diaphragm mainly functions to prevent internal short circuits in the battery and provide channels for the movement of lithium ions as an electrolyte carrier. The diaphragm has an extremely important influence on the use environment, specific capacity, safety performance, and service life of lithium-ion batteries. Therefore, research and development of diaphragms with excellent performance and simple preparation methods that are suitable for industrial production is an important direction to improve the application of lithium-ion batteries.

[0003] Currently, commercial lithium-ion battery separators are mostly porous polymer membranes made of polypropylene and polyethylene. Polymer materials have excellent porosity, and their tensile properties and strength are suitable for existing product preparation methods. The disadvantage is that polyolefin separators will shrink at high temperatures, resulting in direct contact between the positive and negative electrodes, causing safety issues, and polyolefin-based membranes have poor liquid absorption capacity. Warm membranes made of materials such as fibrous non-woven fabrics have better wettability to electrolytes, but have problems such as poor mechanical strength. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium ion battery diaphragm on the basis of the prior art, comprising a main substrate and a mixed slurry layer vacuum impregnated on the surface of the main substrate, wherein the main substrate is a diaphragm paper substrate made of polyolefin fiber, cellulose fiber and dispersant; the mixed slurry layer is made of phenolic resin, curing agent, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer; the main substrate selects cellulose fiber doped with polyolefin fiber, which can improve the toughness and mechanical properties of the diaphragm, effectively avoid battery short circuit caused by lithium dendrite puncture, and improve the safety performance and service life of the lithium ion battery; doping with ceramic powder can further improve the mechanical properties and high temperature resistance of the diaphragm, while eliminating the coating process and improving efficiency; KH550 is used to modify barium titanate to improve the dispersibility of barium titanate and enhance its interface with resin and the gas generation problem of inorganic powder during battery use; adding perfluoroethylene propylene copolymer can reduce the friction coefficient of the diaphragm and effectively reduce the friction loss inside the battery.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned lithium ion battery separator.

[0006] The technical solution of the present invention is as follows:

[0007] The present invention provides a diaphragm for lithium ion batteries, comprising a main substrate and a mixed slurry layer vacuum impregnated on the surface of the main substrate, wherein the main substrate is a diaphragm paper substrate made of polyolefin fibers, cellulose fibers and a dispersant; and the mixed slurry layer is made of phenolic resin, a curing agent, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer (FEP).

[0008] For the present invention, the dispersant is one or more of polyethylene oxide (FEP), polyacrylamide, methyl cellulose or hydroxyethyl cellulose, preferably polyethylene oxide; the curing agent is hexamethylenetetramine. The ceramic powder is one or more of alumina, boehmite, silicon dioxide, barium sulfate, magnesium oxide or aluminum hydroxide, preferably, the ceramic powder is alumina, boehmite or barium sulfate; the modified barium titanate is prepared by chemical reaction of barium titanate and KH550.

[0009] In the present invention, the weight ratio of polyolefin fiber to cellulose fiber is 1-0.1:3, preferably 1:0.5-2, and may be but not limited to 1:0.5, 1:1.25 or 1:2.

[0010] The weight ratio of the total amount of polyolefin fibers and cellulose fibers to the dispersant is 1-5:15, preferably 1:8-12, and may be but not limited to 1:8, 1:10 or 1:12.

[0011] In a preferred embodiment, the preparation method of modified barium titanate comprises the following steps: uniformly mixing barium titanate, solvent and KH550 by ultrasonication, carrying out chemical reaction at 40-50° C., washing and drying to obtain modified barium titanate.

[0012] For the present invention, the mass ratio of barium titanate to KH550 is 1-3:0.1-0.5, preferably 2:0.3. The reaction temperature is 40-50° C., preferably 45° C. The reaction time is 4-8 hours, preferably 6 hours.

[0013] The solvent is one or more of methanol, ethanol, isopropyl ketone or acetone, preferably ethanol.

[0014] In the present invention, the lithium ion battery diaphragm provided by the present invention comprises a main substrate and a mixed slurry layer vacuum impregnated on the surface of the main substrate, wherein the main substrate is a diaphragm paper substrate made of polyolefin fibers, cellulose fibers and a dispersant; the mixed slurry layer is made of phenolic resin, a curing agent, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer, wherein the mixed slurry layer comprises the following components in parts by weight: 15-25 parts of phenolic resin, 0.1-0.8 parts of hexamethylenetetramine, 15-45 parts of ceramic powder, 4-15 parts of modified barium titanate and 4-20 parts of perfluoroethylene propylene copolymer; wherein the weight ratio of the total amount of polyolefin fibers and cellulose fibers to the phenolic resin is 9:15-25.

[0015] In a preferred embodiment, the mixed slurry layer includes the following components in parts by weight: 20 parts of phenolic resin, 0.3-0.5 parts of hexamethylenetetramine, 23-35 parts of ceramic powder, 7-8 parts of modified barium titanate and 8-11 parts of perfluoroethylene propylene copolymer; wherein the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:20.

[0016] In a more preferred embodiment, the mixed slurry layer comprises the following components in parts by weight:

[0017] For example, 20 parts of phenolic resin, 0.3 parts of hexamethylenetetramine, 35 parts of aluminum oxide, 7 parts of modified barium titanate and 8 parts of perfluoroethylene propylene copolymer; wherein the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:20.

[0018] 20 parts of phenolic resin, 0.5 parts of hexamethylenetetramine, 23 parts of boehmite, 7 parts of modified barium titanate and 10 parts of perfluoroethylene propylene copolymer; wherein the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:20.

[0019] 20 parts of phenolic resin, 0.5 parts of hexamethylenetetramine, 23 parts of barium sulfate, 8 parts of modified barium titanate and 11 parts of perfluoroethylene propylene copolymer, wherein the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:20.

[0020] The present invention also provides a method for preparing the above-mentioned lithium ion battery separator, which comprises the following steps:

[0021] (1) mixing barium titanate, solvent and KH550 uniformly by ultrasonication, carrying out chemical reaction at 40-50° C., washing and drying to obtain modified barium titanate;

[0022] (2) dissolving a dispersant in a solvent to prepare a dispersion, adding polyolefin fibers and cellulose fibers to the obtained dispersion, dispersing them uniformly, filtering out the dispersion, and obtaining a separator paper substrate;

[0023] (3) adding phenolic resin, curing agent, ceramic powder, modified barium titanate and perfluoroethylene propylene into a solvent, stirring evenly to obtain a mixed slurry;

[0024] (4) Vacuum impregnating the diaphragm paper substrate obtained in step (2) and the mixed slurry obtained in step (3), and drying to obtain a diaphragm.

[0025] For the present invention, in step (1), the mass ratio of barium titanate to KH550 is 1-3:0.1-0.5, preferably 2:0.3. The reaction temperature is 40-50° C., preferably 45° C. The reaction time is 4-8 hours, preferably 6 hours.

[0026] In step (1), the solvent is one or more of methanol, ethanol, isopropyl ketone or acetone, preferably ethanol.

[0027] In step (3), the solvent is one or more of methanol, ethanol, isopropyl ketone or acetone, preferably ethanol.

[0028] For the present invention, the dispersant is one or more of polyethylene oxide, polyacrylamide, methyl cellulose or hydroxyethyl cellulose, preferably polyethylene oxide; the curing agent is hexamethylenetetramine; the ceramic powder is one or more of alumina, boehmite, silica, barium sulfate, magnesium oxide or aluminum hydroxide, preferably, the ceramic powder is alumina, boehmite or barium sulfate.

[0029] Adopt the technical scheme of the present invention, the advantages are as follows:

[0030] The invention provides a diaphragm for lithium ion batteries, comprising a main substrate and a mixed slurry layer vacuum impregnated on the surface of the main substrate, wherein the main substrate is a diaphragm paper substrate made of polyolefin fiber, cellulose fiber and a dispersant; the mixed slurry layer is made of phenolic resin, hexamethylenetetramine, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer; the main substrate selects cellulose fiber doped with polyolefin fiber, which can improve the toughness and mechanical properties of the diaphragm, effectively avoid battery short circuit caused by lithium dendrite puncture, and improve the safety performance and service life of the lithium ion battery; doping with ceramic powder can further improve the mechanical properties and high temperature resistance of the diaphragm, and at the same time save the coating process and improve the efficiency; KH550 is used to modify the barium titanate, improve the dispersibility of the barium titanate and enhance its interface effect with the resin and the gas generation problem of the inorganic powder during the use of the battery; adding the perfluoroethylene propylene copolymer can reduce the friction coefficient of the diaphragm and effectively reduce the friction loss inside the battery. DETAILED DESCRIPTION

[0031] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0032] Example 1

[0033] A lithium-ion battery separator comprises a main substrate and a mixed slurry layer vacuum-impregnated on the surface of the main substrate, wherein the main substrate is a separator paper substrate made of polyolefin fiber, cellulose fiber and a dispersant; the mixed slurry layer is made of phenolic resin, hexamethylenetetramine, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer, wherein the weight ratio of polyolefin fiber to cellulose fiber is 1:0.5, the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the dispersant is 1:8, and the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:20. The specific preparation method is as follows:

[0034] (1) 2 g of barium titanate was added to 100 g of ethanol, and after stirring, 6 g of 5% KH550 ethanol solution was added to the mixture, and ultrasonic mixing was performed for 1 h. After mixing, a chemical reaction was carried out at 45° C. for 6 h. The obtained powder was repeatedly washed with pure water and dried in an oven at 60° C. to obtain modified barium titanate;

[0035] (2) The dispersant polyethylene oxide (FEP) is dissolved in ethanol to prepare a dispersion with a concentration of 4 wt%. 6 g of polyolefin fiber and 3 g of cellulose fiber are added to the obtained 1.8 kg of dispersion. A fiber defibering machine is used to defiberize and disperse the fibers. After the dispersion is evenly dispersed, the dispersed fibers are poured into a papermaking machine. The dispersion is filtered to obtain a diaphragm paper substrate, which is then dried at 60°C.

[0036] (3) adding 20 g of phenolic resin, 0.3 g of hexamethylenetetramine, 35 g of aluminum oxide, 7 g of modified barium titanate and 8 g of perfluoroethylene propylene copolymer (FEP) to 250 g of ethanol, stirring evenly to obtain a mixed slurry;

[0037] (4) The diaphragm paper substrate obtained in step (2) and the mixed slurry obtained in step (3) are placed in a vacuum impregnation kettle container, and vacuum is drawn to make the kettle in a negative pressure state, and vacuum impregnation is performed for 5 minutes. The diaphragm is taken out and hot-pressed and dried to obtain the diaphragm.

[0038] Example 2

[0039] A lithium-ion battery separator comprises a main substrate and a mixed slurry layer vacuum-impregnated on the surface of the main substrate, wherein the main substrate is a separator paper substrate made of polyolefin fiber, cellulose fiber and a dispersant; the mixed slurry layer is made of phenolic resin, hexamethylenetetramine, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer, wherein the weight ratio of polyolefin fiber to cellulose fiber is 1:2, the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the dispersant is 1:10, and the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:20. The specific preparation method is as follows:

[0040] (1) 2 g of barium titanate was added to 100 g of ethanol, and after stirring, 6 g of 5% KH550 ethanol solution was added to the mixture, and ultrasonic mixing was performed for 1 h. After mixing, a chemical reaction was carried out at 45° C. for 6 h. The obtained powder was repeatedly washed with pure water and dried in an oven at 60° C. to obtain modified barium titanate;

[0041] (2) The dispersant polyethylene oxide (FEP) is dissolved in ethanol to prepare a dispersion with a concentration of 5 wt%. 3 g of polyolefin fiber and 6 g of cellulose fiber are added to the obtained 1.8 kg of dispersion. A fiber defibering machine is used to defiberize and disperse the fibers. After the dispersion is evenly dispersed, the dispersed fibers are poured into a papermaking machine. The dispersion is filtered to obtain a diaphragm paper substrate, which is then dried at 60°C.

[0042] (3) adding 20 g of phenolic resin, 0.5 g of hexamethylenetetramine, 23 g of boehmite, 7 g of modified barium titanate and 10 g of perfluoroethylene propylene copolymer (FEP) to 220 g of ethanol, stirring evenly to obtain a mixed slurry;

[0043] (4) The diaphragm paper substrate obtained in step (2) and the mixed slurry obtained in step (3) are placed in a vacuum impregnation kettle container, and vacuum is drawn to make the kettle in a negative pressure state, and vacuum impregnation is performed for 5 minutes. The diaphragm is taken out and hot-pressed and dried to obtain the diaphragm.

[0044] Example 3

[0045] A lithium-ion battery separator comprises a main substrate and a mixed slurry layer vacuum-impregnated on the surface of the main substrate, wherein the main substrate is a separator paper substrate made of polyolefin fiber, cellulose fiber and a dispersant; the mixed slurry layer is made of phenolic resin, hexamethylenetetramine, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer, wherein the weight ratio of polyolefin fiber to cellulose fiber is 1:1.25, the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the dispersant is 1:12, and the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:20. The specific preparation method is as follows:

[0046] (1) 2 g of barium titanate was added to 100 g of ethanol, and after stirring, 6 g of 5% KH550 ethanol solution was added to the mixture, and ultrasonic mixing was performed for 1 h. After mixing, a chemical reaction was carried out at 45° C. for 6 h. The obtained powder was repeatedly washed with pure water and dried in an oven at 60° C. to obtain modified barium titanate;

[0047] (2) The dispersant polyethylene oxide (FEP) is dissolved in ethanol to prepare a dispersion with a concentration of 6 wt%. 4 g of polyolefin fiber and 5 g of cellulose fiber are added to the obtained 1.8 kg of dispersion. A fiber defibering machine is used to defiberize and disperse the fibers. After the dispersion is evenly dispersed, the dispersed fibers are poured into a papermaking machine. The dispersion is filtered to obtain a diaphragm paper substrate, which is then dried at 60°C.

[0048] (3) adding 20 g of phenolic resin, 0.5 g of hexamethylenetetramine, 23 g of barium sulfate, 8 g of modified barium titanate and 12 g of perfluoroethylene propylene copolymer (FEP) to 260 g of ethanol, stirring evenly to obtain a mixed slurry;

[0049] (4) The diaphragm paper substrate obtained in step (2) and the mixed slurry obtained in step (3) are placed in a vacuum impregnation kettle container, and vacuum is drawn to make the kettle in a negative pressure state, and vacuum impregnation is performed for 5 minutes. The diaphragm is taken out and hot-pressed and dried to obtain the diaphragm.

[0050] Comparative Example 1

[0051] (1) Dissolve the dispersant polyethylene oxide (FEP) in ethanol to prepare a dispersion with a concentration of 4 wt%, add 9 g of polyolefin fiber to the obtained 1.8 kg dispersion, use a fiber defiberizer to defiberize and disperse, and after uniform dispersion, pour the dispersed dispersion into a papermaking machine, filter out the dispersion, obtain a diaphragm paper substrate, and dry it at 60°C.

[0052] (2) adding 20 g of phenolic resin and 0.3 g of hexamethylenetetramine to 250 g of ethanol and stirring evenly to obtain a mixed slurry;

[0053] (4) The diaphragm paper substrate obtained in step (2) and the mixed slurry obtained in step (3) are placed in a vacuum impregnation kettle container, and vacuum is drawn to make the kettle in a negative pressure state, and vacuum impregnation is performed for 5 minutes. The diaphragm is taken out and hot-pressed and dried to obtain the diaphragm.

[0054] The diaphragms prepared in the examples and comparative examples were subjected to a series of performance tests, and the obtained data are shown in Table 1 below.

[0055] Table 1 Performance test results

[0056] Test items Example 1 Example 2 Example 3 Comparative Example 1 <![CDATA[Air permeability / s·100mL -1 > 170 175 176 145 <![CDATA[Strength / kg·cm -2 > 1500 1700 1450 1000 Friction coefficient 0.69 0.62 0.56 0.8 150℃ heat shrinkage / % 1.7 1.5 1.45 3.5

[0057] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on some of the technical features therein. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A separator for a lithium ion battery, characterized in that: The diaphragm includes a main substrate and a mixed slurry layer vacuum-impregnated on the surface of the main substrate, wherein the main substrate is a diaphragm paper substrate made of polyolefin fiber, cellulose fiber and a dispersant; the mixed slurry layer is made of phenolic resin, a curing agent, ceramic powder, modified barium titanate and perfluoroethylene propylene copolymer; wherein the dispersant is one or more of polyethylene oxide, polyacrylamide, methyl cellulose or hydroxyethyl cellulose; the curing agent is hexamethylenetetramine; the ceramic powder is one or more of alumina, boehmite, silicon dioxide, barium sulfate, magnesium oxide or aluminum hydroxide; and the modified barium titanate is prepared by chemical reaction of barium titanate and KH550.

2. The lithium ion battery separator according to claim 1, characterized in that The dispersant is polyethylene oxide; The ceramic powder is aluminum oxide, boehmite or barium sulfate.

3. The lithium ion battery separator according to claim 2, characterized in that The preparation method of the modified barium titanate comprises the following steps: uniformly mixing barium titanate, a solvent and KH550 by ultrasonication, carrying out a chemical reaction at 40-50° C., washing and drying to obtain the modified barium titanate; wherein the mass ratio of barium titanate to KH550 is 1-3:0.1-0.5, preferably 2:0.3; the reaction temperature is 45° C.; the reaction time is 4-8 hours, preferably 6 hours; the solvent is one or more of methanol, ethanol, isopropyl ketone or acetone, preferably ethanol.

4. The lithium ion battery separator according to claim 3, characterized in that The weight ratio of the polyolefin fiber to the cellulose fiber is 1-0.1:3, preferably 1:0.5-2; the weight ratio of the total amount of the polyolefin fiber and the cellulose fiber to the dispersant is 1-5:15, preferably 1:8-12.

5. The lithium ion battery separator according to claim 4, characterized in that The mixed slurry layer comprises the following components in parts by weight: 15-25 parts of phenolic resin, 0.1-0.8 parts of hexamethylenetetramine, 15-45 parts of ceramic powder, 4-15 parts of modified barium titanate and 4-20 parts of perfluoroethylene propylene copolymer; wherein the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:15-25.

6. The lithium ion battery separator according to claim 5, characterized in that The mixed slurry layer comprises the following components in parts by weight: 20 parts of phenolic resin, 0.3-0.5 parts of hexamethylenetetramine, 23-35 parts of ceramic powder, 7-8 parts of modified barium titanate and 8-11 parts of perfluoroethylene propylene copolymer; wherein the weight ratio of the total amount of polyolefin fiber and cellulose fiber to the phenolic resin is 9:

20.

7. The lithium ion battery separator according to claim 6, characterized in that The mixed slurry layer comprises the following components in parts by weight: 20 parts of phenolic resin, 0.3 parts of hexamethylenetetramine, 35 parts of aluminum oxide, 7 parts of modified barium titanate and 8 parts of perfluoroethylene propylene copolymer; 20 parts of phenolic resin, 0.5 parts of hexamethylenetetramine, 23 parts of boehmite, 7 parts of modified barium titanate and 10 parts of perfluoroethylene propylene copolymer; 20 parts of phenolic resin, 0.5 parts of hexamethylenetetramine, 23 parts of barium sulfate, 8 parts of modified barium titanate and 11 parts of perfluoroethylene propylene copolymer.

8. The method for preparing a lithium ion battery separator according to claim 1, characterized in that: It includes the following steps: (1) mixing barium titanate, solvent and KH550 uniformly by ultrasonication, carrying out chemical reaction at 40-50° C., washing and drying to obtain modified barium titanate; (2) dissolving a dispersant in a solvent to prepare a dispersion, adding polyolefin fibers and cellulose fibers to the obtained dispersion, dispersing them uniformly, filtering out the dispersion, and obtaining a separator paper substrate; (3) adding phenolic resin, curing agent, ceramic powder, modified barium titanate and perfluoroethylene propylene into a solvent, stirring evenly to obtain a mixed slurry; (4) Vacuum impregnating the diaphragm paper substrate obtained in step (2) and the mixed slurry obtained in step (3), and drying to obtain a diaphragm.

9. The method for preparing a lithium ion battery separator according to claim 8, characterized in that: In step (1), the mass ratio of barium titanate to KH550 is 1-3:0.1-0.5, preferably 2:0.3; the reaction temperature is 45° C., and the reaction time is 4-8 hours, preferably 6 hours; in step (1) or step (3), the solvent is one or more of methanol, ethanol, isopropyl ketone or acetone, preferably ethanol.

10. The method for preparing a lithium ion battery separator according to claim 9, characterized in that: The dispersant is polyethylene oxide; the curing agent is hexamethylenetetramine; the ceramic powder is alumina, boehmite or barium sulfate; the weight ratio of the polyolefin fiber to the cellulose fiber is 1-0.1:3, preferably 1:0.5-2; the weight ratio of the total amount of the polyolefin fiber and the cellulose fiber to the dispersant is 1-5:15, preferably 1:8-12; the mixed slurry layer comprises the following components in parts by weight: 15-25 parts of phenolic resin, 0.1-0.8 parts of curing agent, 15-45 parts of ceramic powder, 4-15 parts of modified barium titanate and 4-20 parts of perfluoroethylene propylene copolymer; wherein the weight ratio of the total amount of the polyolefin fiber and the cellulose fiber to the phenolic resin is 9:15-25.

Citation Information

Patent Citations

  • Separator for lithium secondary batteries, and lithium secondary battery using same

    CN102160212A

  • Preparation method of ceramic-modified lithium-ion battery diaphragm

    CN104091910A

  • High-temperature-resistant lithium ion battery diaphragm paper and preparation method thereof

    CN115732854A